Use of Educational Games to Improve Science Learning Outcomes of Elementary School Students: Penggunaan Game Edukatif Untuk Meningkatkan Hasil Belajar IPA Siswa Sekolah Dasar - Rosidatul Amalia; Ruli Astuti (Academia Open, 2023)
This study aims to analyze the use of educational games to improve students learning outcomes of natural science students of class VI in MI Muhammadiyah 2 Kedungbanteng. This study uses quantitative method. By collecting data using observation, documentation, tests, and questionnaires. Data analysis technique used T test. Based on the results of data analysis shows that the effectiveness of the use of educational games on learning outcomes of natural science class VI, it can be seen from the results of the T test (2-tailed) = 0.000 < 0.05, the hypothesis of this research is H0 is rejected and Ha is accepted. . There is a change after the use of educational games can be seen based on the average result before the use of educational games is 63.8 while the average value after the use of educational games is 85. The use of educational games is quite efficient in increasing the learning outcomes of natural science students in grade VI MI Muhammadiyah 2 Kedungbanteng. Highlights: Educational games and learning outcomes: Highlighting the use of educational games to improve the learning outcomes of natural science students in class VI. Quantitative method and data collection: Noting the use of a quantitative approach and data collection techniques such as observation, documentation, tests, and questionnaires. Effectiveness of educational games: Stating the significant improvement in learning outcomes as indicated by the T-test results and the average scores before and after using educational games. Keywords: educational games, learning outcomes, natural science, quantitative method, data analysis